Morphological means of expressing the categorical meaning of the animate / inanimate (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article focuses on the relations between the category of case with the lexico-grammatical category of the animate/inanimate of the nouns. The sequence of expression of substantives’ meaning in singular with the seme «animate» and «inanimate» object is described on the level of genitive, dative and vocative case endings covering the written period of the Ukrainian language development.
Keywords: category of the animate/inanimate; category of case; morphological means; old flexions